Pencarian Rute Terdekat Menghindari Jalan Rusak Menggunakan Algoritma A-Star - Rifki Setiawan (Pusat Riset dan Inovasi Nasional, 2024)
In our daily lives, we are often faced with the challenge of broken roads that can affect our travel. To solve this problem, a web-based map system has been developed. The system uses road data from OpenStreetMap and the A-star algorithm to find the shortest route that avoids bad roads. The website is built using JavaScript, PHP, HTML, and CSS, with the support of a MySQL database that stores information on damaged roads and user accounts. The process of using the system starts with registration and account login. Users can view the map on the main page, report the damaged road with photo evidence equipped with a time watermark and coordinate data, and view their initial route. The admin then validates the damaged road data, and the system automatically constructs an alternative route that avoids the verified damaged roads. The accuracy of the A-star algorithm in finding routes depends on the amount and correctness of the damaged road data entered by the admin. In further development, special attention is paid to admin validation, data security, integration with location service provider APIs, and performance optimization. Richer reporting features, multi-platform support, and notifications to users could also be valuable additions. With good documentation and thorough testing, the system is expected to provide an effective solution and be well received by users.